KORELASI MOTIVASI BELAJAR DENGAN TANGGUNG JAWAB BELAJAR TEMATIK SECARA DARING DI MASA PANDEMI COVID-19 DI SDN 01 SERAMBAI - Bernard Andriano Sukma Pabayo; Kartono Kartono; Suparjan Suparjan (Universitas Tanjungpura, 2021)
AbstractThe purpose of this article was to investigate the correlation between learning motivation and learning responsibility in online thematic learning during the COVID-19 pandemic at SDN 01 Serambai. The method used in this research is a descriptive method in the form of correlation studies. This research is a population study with 40 students. The sample used in this study was class VI A, amounting to 20 people. The data collection technique in this research is Indirect Communication Technique, namely by holding an indirect relationship or by means of an intermediary, namely using a questionnaire. The tool used to collect data is a questionnaire. Data analysis techniques carried out with statistical analysis showed that student learning motivation of 82.15% was included in the very good category and student learning responsibility was 85.85%, and the correlation between learning motivation and learning responsibility was rcount = 0.777 with a significant level. 5% is with N = 20. Then N = 20 is 0.444. Thus, rcount < rtable or 0.777 > 0.444. Based on these data it can be concluded that . This proves that there is a positive correlation between learning motivation and learning responsibility in thematic learning during the COVID19 pandemic at SDN 01 Serambai.Keywords: correlation, learning motivation and learning responsibility